Functionalized Collagen/Elastin‐like Polypeptide Hydrogels for Craniofacial Bone Regeneration. Issue 8 (21st December 2022) - Pal, Pallabi; Tucci, Michelle A.; Fan, Lir‐Wan; Bollavarapu, Ratna; Lee, Jonathan W.; Salazar Marocho, Susana M.; Janorkar, Amol V.
Abstract: Critical‐sized cranial bone defects fail to re‐ossify and require the surgical intervention of cranioplasty. To achieve superior bone healing in such cases, a hydrogel consisting of an interpenetrating network of collagen and elastin‐like polypeptide to encapsulate bone morphogenetic protein‐2 (BMP‐2), doxycycline, and 45S5 Bioglass is developed. This hydrogel has an appropriate elastic modulus of 39 ± 2.2 kPa to allow proper handling during implantation. The hydrogel promotes human adipose‐derived stem attachment, proliferation, and differentiation toward the osteogenic lineage, including the deposition of hydroxyapatite particles embedded within a collagenous fibrillar structure after 21 days of in vitro culture. After eight weeks of implantation of the acellular hydrogel in a critical‐sized rat cranial defect model, only a small quantity of various pro‐inflammatory (< 20 pg mg −1 ) and anti‐inflammatory (< 10 pg mg −1 ) factors in the adjacent cranial tissue is noticed, indicating the overall biocompatibility of the hydrogel. Scanning electron microscopy evidenced the presence of new fibrous extracellular matrix and mineral aggregates at the defect site, with calcium/phosphorus ratio of 0.5 and 2.0 by eight and twelve weeks, respectively. Microcomputed tomography (Micro‐CT) and histological analyses showed formation of mature mineralized tissue that bridged with the surrounding bone. Taken together, the acellular composite hydrogel shows great promise for superior bone healing after cranioplasty. Abstract : A collagen/elastin‐like polypeptide hydrogel encapsulating bone morphogenetic protein‐2 (BMP‐2), doxycycline, and 45S5 Bioglass promotes human adipose‐derived stem attachment, proliferation, and differentiation in vitro toward the osteogenic lineage. Implantation of the hydrogel in a critical‐sized rat cranial defect forms a mature mineralized tissue that bridges with the surrounding bone, indicating promise for superior bone healing after cranioplasty.